Clear cell lesions in pathology: Histomorphologic approach to diagnosis - Asaranti Kar; Kaumudee Pattnaik; Tushar Kar; Priyadarshini Biswal; Chandraprava Mishra; Lilabati Guru (Wolters Kluwer Medknow Publications, 2020)
There has been remarkable progress in the field of surgical pathology; however, histomorphology has remained the most important and essential tool of the surgical pathologist in everyday practice till now. It is surprising that the hematoxylin-eosin (H and E) stain, introduced more than a century ago, has still remained the gold standard stain for histological examination and diagnosis of human diseases. Besides different findings or clues observed in histopathology sections like inclusions, granules, grooving, globules, halo, or clearing, which would enable the pathologist to provide a precise and accurate diagnosis; observation of clear cells is one of the important findings and clue for reporting. It may also sometimes lead to difficulties and delays in establishing the diagnosis. It can be focal or extensive and primary or rarely it may be secondary. Clear cell changes may be observed in many non-neoplastic, benign, or malignant tumors of diverse origin. Clear cell tumors contain a preponderance of clear cells. It can be seen in almost all the organs of human body and can be classified according to location or biological behavior. Commonly seen clear-cell tumors are usually malignant and common organs involved are female genital tract, urogenital tract, head and neck areas, central nervous system, skin, and rarely in bone and soft tissues. For approach to clear cell lesions, one has to decide if the change is artifactual, a mimic of clear cell tumors, or a clear cell tumor in reality. Once the mimics and artifactual/degenerative changes have been ruled out, a tumor either primarily of clear cell origin or showing secondary change has to be decided. The tumor next is to be diagnosed as benign/malignant and epithelial/mesenchymal based on morphology.